Sosialisasi dan pelatihan pemasaran digital dan pencatatan keuangan secara sederhana pada UMKM di Desa Tanjung Sari - Rangkuti, Yulita Molliq; Karo Karo, Ichwanul Muslim; Ahyar, Khoirul; Wibowo, Adinda; Haraha, Melyana; Natasya, Amanda; Rahayu, Fitri; Mutiara Sihaloho, Laura Adelia; Anggraini, Nisa Putri (TEKMULOGI: Jurnal Pengabdian Masyarakat, 2024)
The development of the digital era encourages business actors to be able to adjust to the times. Currently, there are still many micro, small and medium enterprises (MSMEs) that do not understand digital marketing in developing their business, resulting in going out of business.  Training and mentoring efforts are needed to help MSME entrepreneurs, especially in rural areas, to survive. Tanjung Sari Village, Batang Kuis Subdistrict, North Sumatra has three active MSMEs, Mrs. Nining's MSME with tempeh products, Uban Fiber Decoration MSME, and Keset Kaki. The three MSMEs have limited digital marketing knowledge. This activity aims to train digital marketing for these MSME entrepreneurs and assist them in simple financial accounting. Activities include surveys, socialization and training and evaluation. Training activities include digital marketing and training in making simple financial bookkeeping. The series of activities received positive responses and community satisfaction and are expected to help MSME players survive in the midst of digital marketing trends and support MSME players in developing their businesses in the future.